How the inappropriate learning material affects the writing skill on students of the 1st year in the tourism career at the Bolivar University in Guaranda, Ecuador school year 2007-2008. Alternative proposal (motivating alternative material) - Noboa Larenas, Mariela (2008)
The present investigation was made in Guaranda (Bolivar Ecuador), at the Bolivar s University on students of the first year of tourism career. In the mentioned university about three years ago a particular phenomenon is occurring; the tourism students are having some problems with the English subject. In the statistics of failures we found that 39 % of the students have only a fair academic yield and the 87% of them do not posses writing abilities. The results of this statistics call our special attention in order to analyze the specific problems they have and propose a possible solution to the main problem they have in their English learning process. We found that the poor didactic material they have influence their lack of writing ability, in addition the teachers are not well trained so the students shows a considerable low grade of motivation during the class